The Role of Islamic Finance in Achieving the SDG Number 9: Build Resilient Infrastructure, Promote Sustainable Industrialization and Foster Innovation - Mohammad, Miza Syahmeena; Abduh, Muhamad (Ekonomi Syariah IAIN Kudus, 2022)
The purpose of this research is to investigate the role of Islamic financing in achieving the Sustainable Development Goals (SDGs), specifically Goal 9: develop resilient infrastructure, promote sustainable industrialization, and foster innovation. Using qualitative approaches to integrate data from secondary sources such as the Islamic Financial Services Industry Stability Report, this paper demonstrates how sukuk can be considered as one of the alternative strategies capable of mobilizing financial resources and encouraging investment in infrastructure development projects. The finding shows that sukuk is a crucial factor in supporting the SGDs number 9 by financing infrastructure development projects that might result in sustainable industrialization and foster innovation that focuses on keeping up with technological advancement.